Effects of Harvest Time on Medicinal Qualities of Hemp - Rattanapakdee, Rattanaporn; Thobunluepop, Pitipong; Anusonpornperm, Somchai; Chaisan, Tanapon; Pongtip, Artit; Maniin, Pranot; Chitbanchong, Wilasinee; Gorinstein, Shela (Journal of Current Science and Technology, 2024)
Harvest time impacts the physicochemical properties of hemp. This study investigated the relationship between harvest time on growth parameters, physiological parameter, and color, in addition to Cannabidiol (CBD), Tetrahydrocannabinol (THC) and Cannabigerol (CBG) concentrations. Siskiyou cannabis was harvested at 5 different stages after flowering 50% at week five to week nine. The rational explanation for stages on growth parameters, physiological parameters, color, and total physiochemical properties was found, while total color changes ranged from brightness (L*) decreased gradually from 66.06 at 5 weeks to a minimum of 16.14 at 9 weeks of flowering. On the contrary, the redness (a*) and yellowness (b*) increased from –0.65 and 8.95 at 5 weeks to their peak values of 19.99 and 34.24 at 9 weeks, respectively. The hue also decreased from 110.03 at 5 weeks to a minimum of 80.14 at 9 weeks, with samples being significantly (p <0.05) different. Tetrahydrocannabinol (THC) was higher than 1 % at week 5, which was lower than their Cannabidiol (CBD) concentrations, reaching 14.35% at week 8. Cannabigerol (CBG) in dried samples reached 2.01% at week 7. The average dry weight of inflorescence per plant peaked at 36.75 g in week 8 and week 9 respectively. Significant differences in Crop Growth Rate (CGR) were noted across the harvesting periods, notably 17.13 and 16.70 g cm⁻² day⁻¹ at weeks 8 and 9, respectively, representing the highest dry weight accumulation per unit area. This increase in dry weight accumulation indicates higher efficiency. Finally, the Harvest Index (HI) showed notable discrepancies among the post-flowering harvesting times, with the greatest total dry weight observed at 0.357 and 0.345 at weeks 8 and 9, respectively. These findings could be of industrial relevance for improving post-harvest processes while maintaining the quality of this regulated crop.